Politiques et pratiques foncieres et engagement des jeunes dans la production de l'igname (dioscorea spp) en Republique du Benin - Rosaire, A.; Abdoulaye, Tahirou; Bernard, F. (European Scientific Institute, ESI, 2022)
Yam cultivation, which is very demanding in terms of soil fertility, is increasingly confronted with the scarcity of fertile land in Benin. This paper focuses on analyzing the influence of land policies and practices on youth engagement in yam production in the Republic of Benin. Data were collected using questionnaires administered to 383 yam producers in the Collines Department identified according to a reasoned choice sampling. The results show that the current land policies in Benin are based on Law No. 2013-01 of August 14, 2013, amended by Law No. 2017-15 on the Land and State Code in the Republic of Benin. This code, without calling into question the customary land rights, promotes the administrative recognition of rights to land through the issuance of a land ownership certificate. Current land practices are based on the principle that land is a sacred and common heritage of humanity. The most common mode of access in the department is inheritance (55%). Land laws and state and local institutions have in common the advantage of guaranteeing access to agricultural land and especially the security of land ownership (R2 = 0.988). As for habits and customs and traditional institutions, they have in common the merit of facilitating access to land (R2 = 0.997). However, current land policies and practices in the Collines department have weaknesses such as the monolingualism of the texts, the oral nature of the clauses, the low level of functioning of land management institutions, corruption, transhumance, the system yam production, and the development of plantations.